STRATEGI KOMUNIKASI DAKWAH PERSUASIF PRIMA DMI DALAM MEMBINA REMAJA MASJID DI NAGARI PANINGGAHAN KEC. JUNJUNG SIRIH KAB.SOLOK - Salvikar, Nanda; Marhen; Ismiati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The main issue in this thesis is the persuasive da'wah communication strategy implemented by PRIMA DMI in guiding mosque youth in Nagari Paninggahan, Junjung Sirih District, Solok Regency. The purpose of this research is to explain how PRIMA DMI identifies its audience, formulates messages, determines methods for guiding mosque youth, and how it utilizes media to deliver da'wah messages. Additionally, it seeks to identify the success factors and challenges faced by PRIMA DMI in delivering its da'wah messages. This research adopts a qualitative approach, with data collection techniques including observation, interviews, and documentation. The research informants consist of the General Chairperson, PRIMA DMI administrators, and mosque youth. The data analysis technique follows a process of data collection, data display, data reduction, verification, and conclusion drawing. To ensure data validity, the triangulation method is applied. The research findings reveal: (1) PRIMA DMI employs a creative communication strategy in identifying its audience by recognizing the character, needs, and interests of youth, using casual and relatable language. (2) PRIMA DMI formulates engaging, educational, and inspirational messages by embedding Islamic values and emphasizing their benefits to youth, using a persuasive approach through real-life stories and inspirational figures. (3) In determining methods, PRIMA DMI applies persuasive and emotional communication, using casual language, humor, and creative social media content to attract mosque youth, build emotional bonds, and encourage participation in Islamic activities. (4) PRIMA DMI utilizes digital media and community-based activities to spread da'wah, foster togetherness, and support the spiritual and social growth of mosque youth. (5) PRIMA DMI's success is driven by its community-based approach, effective use of digital media, and engaging, creative, and interactive da'wah strategies. However, it also faces challenges such as modern lifestyle distractions, limited resources, diverse youth characteristics, and the negative influence of social media content in its da'wah efforts.